2013
DOI: 10.1089/jop.2012.0116
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness and Glaucoma Treatment: An Italian Multicenter Cross-Sectional Study

Abstract: No significant difference in CCT was found between patients treated with PGA and TCAI, suggesting that these topical medications did not statistically and clinically change the CCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…In healthy corneas there was no effect on the endothelium [100]. In POAG, an increase [101] and no change [98] in CCT both have been reported.…”
Section: Topical Medicationsmentioning
confidence: 90%
See 1 more Smart Citation
“…In healthy corneas there was no effect on the endothelium [100]. In POAG, an increase [101] and no change [98] in CCT both have been reported.…”
Section: Topical Medicationsmentioning
confidence: 90%
“…An increase in CCT can also occur as reported in brimatoprost and latanoprost [97]. Iester et al showed no change to CCT in their Italian Glaucoma Register study [98]. No factor has been identified to explain the difference; however, many of those reporting a decrease have had more NTG patients.…”
Section: Topical Medicationsmentioning
confidence: 93%
“… 18 , 19 These findings were consistent with those of De Paoli et al as an interim analysis of a phase II multicenter study presented at a European Society for Medical Oncology conference. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Yet, we measured CCT using Pentacam, which is not the standard (even if there are reports suggesting that it correlates well with the gold standard, ie ultrasound pachimetry [ 27 , 28 ]). Further studies are needed to better understand the relationship between CCT and IOP measurements, in particular those obtained with ART, as it is complex and incompletely determined in both normal subjects and glaucoma patients [ 29 - 31 ].…”
Section: Discussionmentioning
confidence: 99%